(untitled) (Ustozlar uchun, 2026)
Multiple factors contribute to the development of periodontal diseases, causing significant medical and social concerns. The microcirculatory bed of the periodontal area is vital for metabolic control and rapid response to systemic changes. Inflammatory processes in the periodontium lead to microvascular alterations, including vasodilation and increased blood flow velocity. While Laser Doppler Flowmetry (LDF) has been used for decades, it faces limitations such as operator pressure on the examination site, probe angle sensitivity, and high equipment costs. Ultrasound Dopplerography (USDG) offers a non-contact, more adjustable alternative for collecting diagnostic data, particularly for asymptomatic stages and the continuous evaluation of treatment efficacy.